«Forse non è più tempo di vacanza». Records, translations and unpublished autographs from the correspondence between Vittorio Sereni and Ariodante Marianni (1959-1982) (Prassi Ecdotiche della Modernità Letteraria, 2024)
The rich correspondence between Vittorio Sereni and the translator and poet Ariodante Marianni allows to retrace the key moments of a profound friendship that lasted more than twenty years. The essay delves into the most relevant human and literary experiences shared between these two figures both in public and in private contexts. Moreover, between 1959 and 1961, Sereni sent Marianni some early versions of poems later included in his collection Gli strumenti umani. A philological appendix focused on these unpublished autographs is added at the end of the paper.
Keywords: Vittorio Sereni; Ariodante Marianni; Marsia Cristina Campo; William Carlos Williams; Alfredo Giuliani; Neoavanguardia; Festival of the Two Worlds; Gli strumenti umani; Italian Contemporary Poetry; Variants; Composition; Authorial philology